The Integrative Taxonomic Approach Applied to Porifera: A Case Study of the Homoscleromorpha - Boury-Esnault, N.; Lavrov, D.V.; Ruiz, C.A.; Pérez, T. (Integrative and Comparative Biology, 2013)
The two main scientific tasks of taxonomy are species’ delineation and classification. These two tasks are often treated differently, with classification accomplished by newly-developed phylogenetic methods, often based on molecular sequences, while delimitation of species is conducted by what is often considered to be an ‘‘old-fashioned’’ typological approach based on morphological description. A new ‘‘integrative taxonomy’’ has been proposed which maintains that species delimitation should be a multidisciplinary undertaking combining several independent datasets. Here we argue that the same principle is relevant to the classification of species. In the past 20 years, we assembled various datasets based on the external morphology, anatomy, cytology, spicule shapes, geography, reproduction, genetic sequences, and metabolomics of homoscleromorph sponges. We show how we used these datasets to describe new species of homoscleromorph sponges and to elucidate their phylogenetic relationships and their phylogenetic position within the phylum Porifera.